Načrtovanje obnove gozda po velikih poškodbah - Vilhar, Urša (Gozdarski vestnik, 2013)
Restoration of forests affected by large-scale disturbances is a priority task of public forest service and forest owners. Damaged forests should be restored as soon as possible in order to provide their ecosystem services in full extent. This paper deals with the state and perspectives of implementation plans for restoration of forests affected by large-scale disturbances in Slovenian forests. Given the problems of forest restoration after large-scale disturbances we address the priorities of the implementation planning which should be incorporated in future legislation of the forestry sector, related to the restoration of large-scale disturbances in forests. Selected studies on alteration of forest site conditions after large-scale disturbances are presented, including forest fires in Kras, bark beetle attack and wind throw in anthropogenic spruce stand on Pohorje and windthrow in virgin forest remnant Rajhenavski Rog in Kočevski Rog.
Keywords: gozdovi; poškodbe; obnova; rastišče; sanacijski načrti